Visual analysis of drug research and development based on artificial intelligence - Wei Wei; Chao Song; Changxing Qi; Xin Zhang; Xiaoyi Zhang; Run Pu; Yi Ao (Journal of Holistic Integrative Pharmacy)
The iteration of artificial intelligence (AI) technology provides new opportunities for drug research and experimental development. In recent years, AI-based drug research has continuously made new progress and has garnered widespread attention. This study retrieved data from a total of 23,096 papers in AI-based drug research and development from the Web of Science up to May 14, 2024, and conducted bibliometric analysis using VOSviewer software. The results indicated that the AI-based drug research and development is a globally recognized hotspot, and the United States holds a certain authority in this field, while China ranks second in total publication output. The integration of AI technology with drug development primarily involves four stages: drug discovery, preclinical research, clinical trials, and drug manufacturing. So, AI technology has been applied throughout the entire process of drug development. AI-based virtual drug screening and structure-activity relationship analysis started early, while graph neural networks, pre-trained models (Transformer), interpretable AI technology, ChatGPT, and large language models were significantly highlighted in the last 3 years. Moreover, since 2020, AI-based drug repurposing, molecular dynamics simulation, 3D printing, and drug delivery system design have emerged as research hotspots and have been mainly applied to, particularly, on COVID-19, disease prognosis, liver cancer, lung cancer, and immunotherapy.